The high immunogenicity induced by modified sporozoites' malarial peptides depends on their phi (?) and psi (?) angles (2012)
The importance of CSP- and STARP-derived ? and ? dihedral angles in mHABP structure was analysed by 1H NMR in the search for molecules which can be included as components of a first-line-of-defence Plasmodium falciparum sporozoite multi-epitope vaccine against the most lethal form of human malaria. Most of the aforementioned dihedral angles were left-hand-like polyproline type II (PPIIL) structures whilst others had right-hand-like ?-helix (?R), thus allowing mHABPS to fit better into MHCII molecules and thereby form an appropriate pMHCII complex and also establish the H-bonds which stabilise such complex and by this means induce an appropriate immune response. This information has great implications for vaccine development, malaria being one of them. © 2012 Elsevier Inc.